The Role of human capital in pre-industrial societies: skills and earnings in eighteenth-century Castile (Spain) - Bergo\~na Álvarez; Fernando Ramos Palencia (European Historical Economics Society (EHES), 2016)
Using the Ensenada Cadastre, a unique database on Castilian households circa 1750, we measure the effect of human capital on the structure of male labor earnings. Human capital is proxied by individual indicators of basic skills (literacy and numeracy) and of occupational skills. We employ a Mincerian regression approach and find that, on average, workers with greater skills earned more than otherwise similar workers with lesser skills. This finding is robust to the inclusion of additional controls for age, household composition, job characteristics, and place of residence. Estimated returns were larger for urban than for rural workers and were strongly heterogeneous across activity sectors. The richness of our data set reveals that higher-skilled workers not only reaped positive rewards in their main jobs but also were more likely to diversify and increase their earnings through "by-employment". However, not all workers benefited to the same degree from increased human capital. Quantile regression analysis shows that earnings disparities between workers with different skills were much smaller at the lower than at the upper end of the earnings distribution. This evidence indicates that, in pre-industrial Castile, human capital contributed to earnings (and income) inequality.
Keywords: N33; J24; C21; 330; human capital; pre-industrial Spain; skill premia; earnings inequality; quantile regression